2021
DOI: 10.1186/s12889-021-11805-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity and sedentary behaviors with child mental well-being during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic resulted in public health and policy measures to reduce in-person contact and the transmission of the virus. These measures impacted daily life and mental well-being (MWB). The aims of this study were to explore the MWB impacts of COVID-19 on children and assess the associations among perceived changes in physical activity (PA) and sedentary behaviors (SB), with perceived MWB changes, using a mixed-methods approach. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 52 publications
1
37
0
2
Order By: Relevance
“…Previous research suggests that 110–165 daily excess calories result in excess weight gain over a 10 year period among US children [ 17 ]. Recent evidence also suggests that children may have been less physically active and engaged in more sedentary behavior during school closures, which may further exacerbate concerns about unintended weight gain [ 16 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that 110–165 daily excess calories result in excess weight gain over a 10 year period among US children [ 17 ]. Recent evidence also suggests that children may have been less physically active and engaged in more sedentary behavior during school closures, which may further exacerbate concerns about unintended weight gain [ 16 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in recent years, the lifestyles of people around the world have significantly changed during the COVID-19 pandemic, and it has been reported that their changes have a significant impact on well-being and physical activity. Gilbert [51] indicated that there was an association between COVID-19 restrictions and reduced PA.…”
Section: Discussionmentioning
confidence: 99%
“…Having a better understanding of these changes in child activities and PH and MH during the pandemic is important for three main reasons. First, changes in child and adolescent activities are associated with changes in child and adolescent PH and MH, potentially creating an unhealthy feedback loop between changes in activities and changes in health [ 1 , 23 , 24 , 25 , 26 ]. For example, research has shown that outdoor activities and taking part in extracurriculars (e.g., group sports) may increase physical activity and benefit child development, potentially improving PH and MH [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%